A hybrid phantom system for patient skin and organ dosimetry in fluoroscopically guided interventions. Issue 9 (28th July 2017) - Borrego, David; Siragusa, Daniel A.; Balter, Stephen; Bolch, Wesley E.
Abstract : Purpose: The purpose of this study was to investigate calibrations for improved estimates of skin dose and to develop software for computing absorbed organ doses for fluoroscopically guided interventions (FGIs) with the use of radiation dose structured reports (RDSR) and the UF/NCI family of hybrid computational phantoms. Methods and materials: Institutional review board approval was obtained for this retrospective study in which ten RDSRs were selected for their high cumulative reference air kerma values. Skin doses were computed using the University of Florida's rapid in‐clinic peak skin dose algorithm (or UF‐RIPSA). Kerma‐area product (KAP) meter calibrations and attenuation of the tabletop with pad were incorporated into the UF‐RIPSA. To compute absorbed organ doses the RDSRs were coupled with software to develop Monte Carlo input decks for each irradiation event. The effects of spectrum matching were explored by modeling (a) a polychromatic x‐ray energy beam made to match measured first half‐value layers of aluminum, (b) an unmatched spectrum, (c) and a mono‐energetic beam equivalent to the effective x‐ray energy. The authors also considered the practicality of computing organ doses for each irradiation event within a RDSR. Results: The KAP meter is highly dependent on the quality of the x‐ray spectra. Monte Carlo based attenuation coefficients for configurations in which the beam is transmitted through the tabletop with pad reduced the amount by which the software overestimated skin doses. For absorbed organ dose computations, the average ratios of computed organ doses for a non‐fitted to fitted spectrum and effective energy to fitted spectrum were 0.45 and 0.03, respectively. Monte Carlo simulations on average took 38 min per patient. All in‐field organ tallies converged with a relative error of less than 1% and out‐of‐field organs tallies within 10% relative error. Conclusions: This work details changes to the UF‐RIPSA software that include an expanded library of computational phantoms, attenuation coefficients for tabletop with pad, and calibration curves for the KAP meter. For the computation of absorbed organ dose, it is possible to model each irradiation event separately on a patient‐dependent model that best morphometrically matches the patient, thus providing a full report of internal organ doses for FGI patients.